Computer systems: Digital design, fundamentals of computer architecture and assembly language - Elahi, Ata (Springer International Publishing, 2018)
This textbook covers digital design, fundamentals of computer architecture, and assembly language. The book starts by introducing basic number systems, character coding, basic knowledge in digital design, and components of a computer. The book goes on to discuss information representation in computing; Boolean algebra and logic gates; sequential logic; input/output; and CPU performance. The author also covers ARM architecture, ARM instructions and ARM assembly language which is used in a variety of devices such as cell phones, digital TV, automobiles, routers, and switches. The book contains a set of laboratory experiments related to digital design using Logisim software; in addition, each chapter features objectives, summaries, key terms, review questions and problems. The book is targeted to students majoring Computer Science, Information System and IT and follows the ACM/IEEE 2013 guidelines. • Comprehensive textbook covering digital design, computer architecture, and ARM architecture and assembly • Covers basic number system and coding, basic knowledge in digital design, and components of a computer • Features laboratory exercises in addition to objectives, summaries, key terms, review questions, and problems in each chapter
Keywords: ARM architecture; ARM processors; Assembly language; Boolean algebra; Computation theory; Computer architecture; Digital designs; Digital devices; Digital television; Information representation; Laboratory exercise; Laboratory experiments; Number system; Numbering systems; Reviews; Sequential logic; Textbooks; dept.csc

ARM Cortex-M3 Processor and MBED NXP LPC1768 - Elahi, Ata; Arjeski, Trevor (ARM Assembly Language with Hardware Experiments, 2015)
ARM offers variety of the core processor base on their applications and they are: Cortex A series: Cortex A series is a High performance processor for open operating system, the Cortex-A50 is a 64 bit process, application of Cortex-A series are Smart phones, Netbook, Digital TV, and eBook readers
Keywords: dept.csc

ARM Assembly language programming Using Keil Development Tools Introduction - Elahi, Ata; Arjeski, Trevor (ARM Assembly Language with Hardware Experiments, 2015)
Manufacturers of CPUs publish a document that contains information about the processor that includes: list of registers, function of each register, size of data bus, size of address bus and list of instructions that can be executed by the CPU. Each CPU has a known instruction set that a programmer can use to write assembly language programs. Instruction sets are specific to each type of processor. That being said, Pentium processors use a different instruction set than ARM processors. Using the Instructions a of processor to write a program is called assembly language and function of an assembler is to convert assembly language to machine code (binary) that the CPU can understand.
Keywords: dept.csc

Number Systems and Data Communication - Elahi, Ata; Arjeski, Trevor (ARM Assembly Language with Hardware Experiments, 2015)
In order to understand network technology it is important to know how information is represented for transmission from one computer to another. Information can be transferred between computers in one of two ways: an analog signal or a digital signal.
Keywords: Analog Signal; Binary Number; Digital Signal; Number System; Transmission Method; dept.csc

Logic Gates and Introduction to Computer Architecture - Elahi, Ata; Arjeski, Trevor (ARM Assembly Language with Hardware Experiments, 2015)
The basic components of an Integrated Circuit (IC) is logic gates which made of transistors, in digital system there are three basic logic operations and they are called AND, OR and NOT.
Keywords: dept.csc

ARM Instructions Part I - Elahi, Ata; Arjeski, Trevor (ARM Assembly Language with Hardware Experiments, 2015)
Advanced RISC Machine (ARM) was developed by the Acorn Company. ARM is a leader supplier of microprocessors in the world, ARM develop the core CPU and thousand of suppliers add more functional units to the core. ARM uses two types instruction called Thumb and Thumb-2. Thumb instructions are 16 bits and thumb-2 instructions are 32 bits, currently most ARM processors uses 32 bit instructions.
Keywords: dept.csc

ARM Instructions and Part II - Elahi, Ata; Arjeski, Trevor (ARM Assembly Language with Hardware Experiments, 2015)
The data transfer instructions are used to transfer data from memory to registers and from registers to memory and they are Load (LDR) and Store (STR) instructions.
Keywords: dept.csc

ARM Assembly Language with Hardware Experiments - Elahi, Ata; Arjeski, Trevor (Springer, 2015)
This book provides a hands-on approach to learning ARM assembly language with the use of a TI microcontroller. The book starts with an introduction to computer architecture and then discusses number systems and digital logic. The text covers ARM Assembly Language, ARM Cortex Architecture and its components, and Hardware Experiments using TILM3S1968. Written for those interested in learning embedded programming using an ARM Microcontroller. © Springer International Publishing Switzerland 2015.
Keywords: ARM microcontrollers; ARM processors; Arm cortices; Assembly language; Assembly languages (Electronic computers); Microprocessors; Computer architecture; Computer hardware; Digital logic; Education; Embedded programming; Hardware; Hardware experiment; Microcontrollers; Number system; Numbering systems; Programming; dept.csc; faculty_collection

Zigbee Wireless Sensor and Control Network - Elahi, Ata; Gschwender, Adam (Prentice Hall, 2010)
Topics include: Fundamental wireless concepts: OSI Model, error detection, the ISM Band, modulation, WLAN, FHSS, DSSS, Wireless MANs, Bluetooth ; ZigBee essentials: applications, characteristics, device types, topologies, protocol architecture, and expanded ZigBee PRO features ; Physical layer: includes frequency bands, data rate, channels, data/management services, transmitter power, and receiver sensitivity ; MAC layer: data/management services, MAC layer information base, access methods, and frames ; Network layer: data entities, NIB, device configuration, starting network, addressing, discovery, channel scanning ; Application support sublayer and application layer: includes profiles, cluster format, attributes, device discovery, and binding ; ZigBee network security: includes encryption, trust center, security modes, and security management primitives ; Address assignment and routing techniques ; Alternative technologies: 6lowpan, WirelessHART, and Z-wave.:--pub. desc.
Keywords: Industrial applications; Industrial applications; Radio frequency; Personal communication service systems; Standards; Sensor networks; Low voltage systems; dept.csc; faculty_collection

The internet of things in CS education: current challenges and future potential - Burd, Barry; Elahi, Ata; Russell, Ingrid; Barker, Lecia; Perez, Armando Fermin; Siever, Bill; Divitini, Monica; Parker, Alcwyn; Tudor, Liviana; Guerra, Jorge Guerra (2017)
Keywords: dept.csc